2019
DOI: 10.2185/jrm.3008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise time and musculoskeletal problems in children

Abstract: Objectives: The purpose of this study was to evaluate the relationship between exercise time and musculoskeletal problems and to determine the appropriate amount of exercise for children in both lower- and higher-grade levels of elementary and junior high schools.Materials and Methods: Mark-sheet-type questionnaires were distributed to and collected from all elementary and junior high schools in two cities. We collected 22,494 questionnaires in total. The relationship between exercise time and musculoskeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Other researchers showed the association between AKP and physical activity (20) (21). In a cross-sectional study, Tomaru et al showed that the longer the exercise time, the higher the proportion of OSD in elementary and junior high school students (21). High HSS Pedi-FABS was a signi cant risk for AKP occurrence in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Other researchers showed the association between AKP and physical activity (20) (21). In a cross-sectional study, Tomaru et al showed that the longer the exercise time, the higher the proportion of OSD in elementary and junior high school students (21). High HSS Pedi-FABS was a signi cant risk for AKP occurrence in our study.…”
Section: Discussionsupporting
confidence: 55%
“…The difference between the current study and the previous report may be that the previous study focused only on athletic adolescents, and even the non-OSD subjects had tighter lower limbs-with a mean HBD of 6 cm and SLRA of 71 degrees-compared to our study subjects (mean HBD 1.3 cm, mean SLRA 77 degrees). Other researchers showed the association between AKP and physical activity (20) (21). In a cross-sectional study, Tomaru et al showed that the longer the exercise time, the higher the proportion of OSD in elementary and junior high school students (21).…”
Section: Discussionmentioning
confidence: 99%
“…Five years have passed since the start of musculoskeletal examinations, and several reports on musculoskeletal functions have been published. Based on the report that many findings are related to flexibility, such as standing trunk flexion and limited range of motion of the ankle joint 8 ) , and on the results of our study 6 , 9 , 10 ) , we thought that the standing trunk flexion test, which is one of the recommended items of the checklist for musculoskeletal examination, could be an objective indicator of musculoskeletal function. Initially, we expected that there would be a difference in the results of the functional assessment of standing trunk flexion depending on the period of absence from school or relative inactivity.…”
Section: Discussionmentioning
confidence: 69%
“…The difference between the current study and previous studies may be that the previous study focused only on athletic adolescents because even the participants without knee pain had tighter lower limbs, with a mean HBD of 6 cm and an SLRA of 71 degrees, compared to our study participants (mean HBD 1.0 cm and SLRA 77 degrees). Other studies have shown an association between patellar and patellar tendon pain and physical activity [ 20 , 21 ]. In a cross-sectional study, Tomaru et al showed that the longer the exercise time, the higher the proportion of knee pain in elementary and junior high school students [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown an association between patellar and patellar tendon pain and physical activity [ 20 , 21 ]. In a cross-sectional study, Tomaru et al showed that the longer the exercise time, the higher the proportion of knee pain in elementary and junior high school students [ 21 ]. This study was the first to evaluate the relationship between physical activity level and knee pain.…”
Section: Discussionmentioning
confidence: 99%